Games People Play : The Psychology of Human Relationships - Berne, Eric (New York Grove Press, Ltd., 1964)
Eric Berne developed the technique of transactional analysis in group therapy, and here presents his findings to the general public in a witty and entertaining best-seller. He shows how people can achieve a new self-awareness by analyzing their behavior in terms of "games." People tend to live their lives by consistently playing out certain games in their interpersonal relationships. They play these games for a variety of reasons: to avoid confronting reality, to conceal ulterior motives, to rationalize their activities, or to avoid actual participation. These games--if they are not destructive--are both desirable and necessary, and here Dr. Berne offers an analysis of 36 common games, which he breaks down into seven major categories.--Adapted from publisher description.
Include Appendix and Index.
Keywords: Social interaction -- Interpersonal relations -- Game theory -- Mothers and daughters -- Single mothers--Psychology -- Teenage girls--Family relationships -- Social role -- Transactional analysis